Doctors and patients to the promotion of healthy lifestyles in primary care - Carlos Calderón G; Laura Balagué G; Álvaro Sánchez P; Gonzalo Grandes O; Josep M. Cortada P (Universidad de Antioquia, 2009)
Objective: To deepen our knowledge of family physician's and patients perceptions of the promotion activities for health behaviors in smoking, exercise, diet and alcohol consumption. Methodology: Qualitative methodology. Information was obtained by conducting two discussion groups with physicians and two with patients who had previously participated in some interventions. Data were analyzed using the sociological discourse model. Validation was carried out by triangulation among researchers. Results: Health promotion activities are differently perceived by doctors and patients depending on their health services and social contexts. These perspectives and contexts can be graphically represented around two axes: the first one interrelates doctors and patients, and the second one between a biomedical and disease oriented pole, and another pole representing a more integral and health oriented vision of promotion. Conclusions: The obtained results allow us to identify the main health and non-health related factors perceived by doctors and patients as influencing their behaviors. The data will also allow for the construction of a framework in which to interpret the meaning of the promotion activities within the relationship of both agents in the context of the Primary Health Care.